2010
DOI: 10.1186/1743-422x-7-348
|View full text |Cite
|
Sign up to set email alerts
|

The Meq oncoprotein of Marek's disease virus interacts with p53 and inhibits its transcriptional and apoptotic activities

Abstract: BackgroundMarek's disease virus (MDV) is an oncogenic herpesvirus, which causes malignant lymphoma in chickens. The Meq protein of MDV, which is expressed abundantly in MDV-infected cells and in Marek's disease (MD) tumor cells, functions as a transcriptional activator and has been proposed to play an important role in oncogenic transformation. Preliminary studies demonstrated that Meq is able to bind p53 in vitro, as demonstrated using a protein-binding assay. This observation prompted us to examine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…Current evidence indicates that MDV has evolved multiple mechanisms to thwart this cellular response to protect cells against apoptosis [26,27]. One of the latest discoveries is that the Meq oncoprotein of MDV inhibited p53-dependent transcription and apoptosis by interacting directly with p53 [26]. In our study, we further found that several genes of p53-dependent apoptosis pathway including CHEK2, CYCS, APAF1, and PERP were downregulated in infected thymuses at 21 and 28 dpi.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Current evidence indicates that MDV has evolved multiple mechanisms to thwart this cellular response to protect cells against apoptosis [26,27]. One of the latest discoveries is that the Meq oncoprotein of MDV inhibited p53-dependent transcription and apoptosis by interacting directly with p53 [26]. In our study, we further found that several genes of p53-dependent apoptosis pathway including CHEK2, CYCS, APAF1, and PERP were downregulated in infected thymuses at 21 and 28 dpi.…”
Section: Discussionsupporting
confidence: 63%
“…Apoptosis has been shown to be a common host cell response to viral infection [25], which is advantageous for the host as it eliminates virus-infected cells. Current evidence indicates that MDV has evolved multiple mechanisms to thwart this cellular response to protect cells against apoptosis [26,27]. One of the latest discoveries is that the Meq oncoprotein of MDV inhibited p53-dependent transcription and apoptosis by interacting directly with p53 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Within this map, we found that MIF, HSP90AA1, NPM1, STMN1(OP18) and VIM can interact with the tumour suppressor protein TP53. It has been reported that the Meq oncoprotein directly interacts with p53 and inhibits p53-mediated transcriptional activity and apoptosis [14]. This scenario could provide an interesting link between MEQ and these proteins and enhance our understanding of MDV pathogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…The transcriptional regulator MEQ is considered to be the major viral oncoprotein of GaHV-2. The MEQ interacts directly with p53 and inhibits p53-mediated transcriptional activity [25]. Both the MMR system and the p53 pathway are critical in the maintenance of genomic integrity [26], [27].…”
Section: Discussionmentioning
confidence: 99%